Evaluasi Smile dalam Pengelolaan Data dan Informasi : ( Studi Kasus BPJS Ketenagakerjaan Cab.Tanjung Morawa ) - Nurul Ifkah Lolona Silalahi; Raissa Amanda Putri (International Forum of Researchers and Lecturers, 2024)
Evaluation of SMILE in Data and Information Management (Case Study of BPJS Employment, Tanjung Morawa Branch) Using the User Compatibility Method. Effective data and information management in financial institutions such as BPJS Employment requires an application system that meets user needs. This research aims to evaluate SMILE at the Tanjung Morawa BPJS Employment Branch using the User Compatibility method, which assesses the extent to which the application meets the user's needs, abilities and expectations. This research method involves a survey of SMILE users at BPJS Employment Tanjung Morawa Branch, taking into account aspects of usability, efficiency and user satisfaction. Data was collected through questionnaires, interviews and direct observation of smile users. The evaluation results show that SMILE at BPJS Employment Tanjung Morawa Branch has a high level of compatibility with users. The research results show that all EUCS independent variables (indicators), consisting of Content (Content), Format (report), Accurancy (accuracy), Timeliness (speed of presentation), Ease of Use (easy to use), which have a significant relationship with user satisfaction SMILE. Users find this application easy to use, improves work efficiency, and meets their expectations regarding data and information management. However, several recommendations for improvement were also put forward, including increased training for users, improved integration with other systems, and improved data security. This study makes an important contribution to further understanding the extent to which SMILE meets user needs in internal environments. The evaluation results and recommendations produced can serve as guidelines for developing and improving smile in the future.